(untitled) (Costos y Gestión, 2025)
Decision-making in agricultural enterprises occurs under conditions of uncertainty and risk. Marginal Analysis is a key tool in this process, as it allows for evaluating the relationship between production volume, price, and cost structure on operating results. In the viticulture sector, few studies have linked Marginal Analysis to Regulated Deficit Irrigation (RDI). Organizations such as CoViAr and INTA provide analyses based on sectoral average costs but do not specifically address the effects of irrigation strategies. This study applied historical variable costing to determine accounting costs for Malbec and Torrontés Riojano grape varieties grown in the Antinaco-Los Colorados Valley, Argentina, under an RDI regime at 50% from veraison to harvest. Through Marginal Analysis, the joint profitability of both varieties was compared. The objective was to analyze the total grape production to determine the operational profit generated and compare treatments to identify the most profitable option. The results showed that RDI reduced yield and negatively impacted variable costs and total contribution margin. Although Malbec achieved higher market prices, the greater productivity of Torrontés Riojano offset this difference, making it the most economically advantageous variety.